Human Adipose Tissue-Derived Stromal Cells Ameliorate Adriamycin-Induced Nephropathy by Promoting Angiogenesis - Xiaodi Zhao; Chengyan Ma; Lijie Li; Yuemei Yang; Sen Zhang; Xiaoli Wang (Organogenesis)
This study is to investigate the therapeutical effect and mechanisms of human-derived adipose mesenchymal stem cells (ADSC) in relieving adriamycin (ADR)-induced nephropathy (AN). SD rats were separated into normal group, ADR group, ADR+Losartan group (20 mg/kg), and ADR + ADSC group. AN rats were induced by intravenous injection with adriamycin (8 mg/kg), and 4 d later, ADSC (2 × 105 cells/mouse) were administrated twice with 2 weeks interval time (i.v.). The rats were euthanized after the 6 weeks’ treatment. Biochemical indicators reflecting renal injury, such as blood urea nitrogen (BUN), neutrophil gelatinase alpha (NGAL), serum creatinine (Scr), inflammation, oxidative stress, and pro-fibrosis molecules, were evaluated. Results demonstrated that we obtained high qualified ADSCs for treatment determined by flow cytometry, and ADSCs treatment significantly ameliorated renal injuries in DN rats by decreasing BUN, Scr and NGAL in peripheral blood, as well as renal histopathological injuries, especially protecting the integrity of podocytes by immunofluorescence. Furthermore, ADSCs treatment also remarkably reduced the renal inflammation, oxidative stress, and fibrosis in DN rats. Preliminary mechanism study suggested that the ADSCs treatment significantly increased renal neovascularization via enhancing proangiogenic VEGF production. Pharmacodynamics study using in vivo imaging confirmed that ADSCs via intravenous injection could accumulate into the kidneys and be alive at least 2 weeks. In a conclusion, ADSC can significantly alleviate ADR-induced nephropathy, and mainly through reducing oxidative stress, inflammation and fibrosis, as well as enhancing VEGF production.